The Effect of Problem-Based Learning Using Geoboard on Cognitive Ability of SDN 8 Mamboro Students - Anggi Kurnia Putri; Zulnuraini; Nurul Kami Sani; Nashrullah; Danti Indriastuti Purnamasari (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2025)
This study aims to investigate the effect of the Problem Based Learning (PBL) model using geoboard media on the cognitive abilities of fourth-grade students at SD Negeri 8 Mamboro, specifically in the mathematics subject focusing on plane figures. Employing a quasi-experimental design with a one-group pretest-posttest approach, the study involved 29 students as the population. The research hypothesis proposed that the PBL model assisted by geoboard media significantly improves students' cognitive abilities. Data were collected through a multiple-choice test consisting of 14 validated questions. Analysis included descriptive statistics, the Shapiro-Wilk normality test, paired sample t-test, and N-gain test. Results revealed a significant increase in cognitive ability, with the mean pretest score rising from 51.51 to 82.48 in the posttest. The paired sample t-test indicated a significance value of 0.001 (p < 0.05) and a t-value of -19.324, confirming the acceptance of the alternative hypothesis and rejection of the null hypothesis. Furthermore, the N-gain score averaged 0.6765, categorized as moderate improvement. These findings demonstrate that implementing the PBL model with geoboard media effectively enhances students' cognitive skills by fostering independent discovery and active engagement in learning